Measuring traveling wave velocity in the basilar membrane as a potential indicator of endolymphatic hydrops in definite Ménière’s disease: a narrative review - Shen, Xingqian; Pan, Hui; Wang, Linlin; Xie, Wen; Leng, Yangming; Liu, Bo; Xiao, Hongjun (Frontiers in Neurology, 2024)
BackgroundThe pathological hallmark of Ménière’s disease is endolymphatic hydrops, which can lead to an increase in basilar membrane stiffness and, consequently, an acceleration of the traveling wave of sound. The cochlear hydrops analysis masking procedure (CHAMP), which is an auditory brainstem response test masked at various frequencies with high-pass noise masking, uses the principle of the traveling wave velocity theory to determine the presence of endolymphatic hydrops.PurposeThis study aimed to review the previous results of the CHAMP, expound the principles and key indicators, and discuss its clinical significance in diagnosing Ménière’s disease.MethodsA narrative review was performed to revisit the principles of the CHAMP test, procedures, and clinical application results in diagnosing Ménière’s disease.ResultsAccording to the published literature, the CHAMP has a specificity of 31–100%, a sensitivity of 28–100%, and a diagnostic accuracy of 30–100% for the diagnosis of Ménière’s disease, including patients with definite, probable, or possible Ménière’s disease in various studies. These inconsistent results were due to subject inclusion criteria, variable settings, waveform identification, and other factors. Nevertheless, as an electrophysiological technique, the CHAMP may have a relatively high diagnostic value in patients with a definite Ménière’s disease.ConclusionThe CHAMP is still potentially useful for studying the pathophysiology of hydropic ear diseases since the procedure can measure the traveling wave velocity of the basilar membrane in the era of imaging to detect endolymphatic hydrops for Ménière’s disease.